Effects of Feeding Distillers Dried Grains with Solubles (DDGS) on Feed Intake and Milk Production Performance of Crossbred Cows - Madhavatar, Mahesh P; Shah, Shailesh V; Wadhwani, Kishan N; Lunagariya, Pravin M; Modi, Rakesh J; Patel, Ashish C (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Present experiment was conducted to study the performance of feeding Distillers Dried Grains with Solubles (DDGS) on milk production on 18 HF × Kankrej (75:25) advance pregnant crossbred heifers, which were distributed into three treatment groups (T1, T2 and T3) comprising of 6 animals each. The total duration of experiment was 300 days. Animals were offered three different types of total mixed rations containing 20, 10 and 0% Soy DOC, and 0, 10 and 20% rice DDGS (RDDGS) in T1, T2 and T3 groups, respectively. The overall mean values of DMI (kg/animal/day, and kg/100 kg body weight) in crossbred cows were 11.81±0.12 and 2.66±0.05, respectively. Average DMIs in T1, T2 and T3 groups of crossbred cows were 11.99±0.23, 11.81±0.22 & 11.62±0.19 kg/animal/day (p>0.05), and 2.82±0.10, 2.60±0.09 & 2.55±0.08 kg/100 kg body weight (p<0.05), respectively. The DMI (kg/100 kg body weight) was significantly (p<0.05) lower in T2 and T3 groups as compared to T1 group. The overall average milk yield and FCM yield at 4% fat irrespective of treatments and periods was found to be 20.92±0.24 and 21.06±0.59 kg/animal/day, respectively. Average milk yield and FCM yield at 4% fat was non-significantly higher in T2 (21.23±0.38 & 21.26±0.42) as compared to T3 (20.84±0.44 & 21.11±0.48) and T1 (20.71±0.43 & 20.78±0.46) groups. Feeding rice DDGS up to 20% in total mixed ration had no adverse effect on feed intake and milk yield of crossbred cows, indicating it can effectively replace soybean DOC in dairy rations.